CONSÉQUENCES DE LA FAIBLE DÉCLARATION DES NAISSANCES SUR LA PROTECTION DE L’ENFANT EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO - Christian Utheki Udongo , (IJRDO - Journal of Social Science and Humanities Research, 2022)
This article has carefully examined the consequences of low birth registration in the city of Kisangani on child protection. The diagnosis revealed that in this city, the birth registration rate remains quite low, like other cities in the Democratic Republic of the Congo.This deficiency has a considerable impact on the protection of the child. These consequences are reflected, in particular, in the persistence of the “unaccompanied child” phenomenon and the use of some in the worst forces of the works.In addition, the low declaration of births makes it difficult to control demographic trends, health protection and the implementation of the policy of free children. The same applies to the difficulty of combating violence against children and early marriage.